2013
DOI: 10.1371/journal.pone.0078279
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Activation of Wnt/β-Catenin Signaling in Lens Fiber Cells Results in Cataract Formation and Aberrant Fiber Cell Differentiation

Abstract: The Wnt/β-catenin signaling pathway controls many processes during development, including cell proliferation, cell differentiation and tissue homeostasis, and its aberrant regulation has been linked to various pathologies. In this study we investigated the effect of ectopic activation of Wnt/β-catenin signaling during lens fiber cell differentiation. To activate Wnt/β-catenin signaling in lens fiber cells, the transgenic mouse referred to as αA-CLEF was generated, in which the transactivation domain of β-caten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…These observations fit very well to published data showing that cataract formation, smaller lenses and inhibited lens cell differentiation can be induced by β-catenin overexpression (Antosova et al, 2013;Shaham et al, 2009;Martinez et al, 2009). Note that overexpression of β-catenin in LFCs alone is sufficient to induce cataract formation (Antosova et al, 2013). Gain of β-catenin function in the central ocular ectoderm suppresses lens formation (Smith et al, 2005), which is in line with the smaller lenses found in our morphants.…”
Section: Sipa1l3 and Wnt Signalingsupporting
confidence: 92%
See 2 more Smart Citations
“…These observations fit very well to published data showing that cataract formation, smaller lenses and inhibited lens cell differentiation can be induced by β-catenin overexpression (Antosova et al, 2013;Shaham et al, 2009;Martinez et al, 2009). Note that overexpression of β-catenin in LFCs alone is sufficient to induce cataract formation (Antosova et al, 2013). Gain of β-catenin function in the central ocular ectoderm suppresses lens formation (Smith et al, 2005), which is in line with the smaller lenses found in our morphants.…”
Section: Sipa1l3 and Wnt Signalingsupporting
confidence: 92%
“…Additionally, Sipa1l3 or Epha4 deficiency resulted in an upregulation of the direct Wnt/β-catenin target axin2, which is in agreement with a previously published study that shows axin2 overexpression upon Wnt/β-catenin activation in mouse lenses (Antosova et al, 2013). These observations fit very well to published data showing that cataract formation, smaller lenses and inhibited lens cell differentiation can be induced by β-catenin overexpression (Antosova et al, 2013;Shaham et al, 2009;Martinez et al, 2009).…”
Section: Sipa1l3 and Wnt Signalingsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results resemble more the phenotype obtained when Axin2, an antagonist of Wnt/β-catenin, is disrupted leading to developmental eye defects such as microphthalmia, lens defects and coloboma including defects in the closure of the OF and ventral OC (Alldredge and Fuhrmann, 2016). Moreover, constitutive activation of Wnt/β-catenin signaling in lens fiber cells results in abnormal and delayed fiber cell differentiation resulting in cataracts and microphthalmia (Antosova et al, 2013). Finally, we have previously observed that nuclear β-catenin+ and p27+ (Cyclin-dependent kinase inhibitor 1B) cells of the RPE do not proliferate suggesting that nuclear β-catenin prevents those cells from entering the cell cycle (Zhu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is urgent to seek the underlying molecular mechanisms of neuronal dysfunction induced by neuroinflammation. Wnt signaling pathway, proven to be involved in a variety of functions in cellular processes, including proliferation, differentiation, and apoptosis (Antosova et al 2013;Wei et al 2013;Xie et al 2014), is closely associated with the development of the CNS embryonic development and the regulation of the adult brain function . In detail, it regulates synaptic plasticity and neurogenesis in the adult nervous system.…”
Section: Introductionmentioning
confidence: 99%